EMPIRICAL ASPECTS OF THE INFLUENCE OF THE COOPERATION OF FISCAL INSTITUTIONS ON PROPERTY TAX ADMINISTRATION - Oksana Desyatnyuk; Andriy Krysovatyy; Bohdana Shuliuk; Fedir Tkachyk; Vadym Maslii (Фінансово-кредитна діяльність: проблеми теорії та практики)
The purpose of this research is to develop scientific and pragmatic approaches to optimize the interaction of fiscal institutions in the process of administering property taxes to local budgets in Ukraine, considering contemporary realities and international experience. Results and Conclusions. The article addresses current issues concerning the interaction between government and local authorities in enhancing property tax administration procedures. It substantiates the theoretical determinants of property taxes and highlights their fiscal role within the tax revenue architecture of local budgets in Ukraine and the European Union. An organizational-methodological framework is improved to ensure the administration mechanism of property taxes in Ukraine across key dominants. Using an empirical approach and comparative analysis, the study reveals a positive trend in the share of property tax elements within the structure of local budget revenues in Ukraine. This trend is attributed to fiscal decentralization and cooperative efforts of fiscal institutions in achieving planned property tax revenue targets. First identified the synergistic fiscal effect of further active collaboration among tax authorities, local governments, and taxpayers in the context of forming and updating property registers in Ukraine for taxation purposes based on a value-based approach. Theoretical and methodical approaches to forecasting property tax revenues to local budgets of Ukraine have been further developed, taking into account fiscal policy trends under martial law and using the «forecasting» module of the SPSS statistics package. This approach made it possible to identify the limited fiscal impact of the real estate tax (excluding land), which does not align with global practices and indicates the incomplete fiscal and regulatory function of this tax in Ukraine. Based on the research results, measures are proposed to optimize property tax administration procedures in Ukraine, grounded in principles of cooperation, transparency, compliance, digitalization, and the use of fiscal registers (cadasters).